Destabilization of β‐Hemocyanin from Helix pomatia in Presence of Choline Amino Acids Results in Improved Cell Specificity and Cytotoxicity against Human Breast Cancer. Issue 39 (21st October 2019) - Guncheva, Maya H.; Todinova, Svetla J.; Uzunova, Veselina P.; Idakieva, Krasimira N.; Raynova, Yuliana M.; Ossowicz, Paula; Janus, Ewa; Tzoneva, Rumiana D.
Abstract: Many hemocyanins, the oxygen‐transporting proteins in some invertebrates, are studied in depth in view of their immunostimulatory and vaccine adjuvant properties. However, their direct cytotoxic effect on breast cancer cell lines is poorly investigated. Here, we evaluated the effect of native β‐hemocyanin from Helix pomatia (β‐HpH) and its complexes with choline amino acids ([Chol][AA]) on the viability and morphology of estrogen‐dependent (MCF‐7) and estrogen‐independent (MDA‐MB‐231) breast cancer cells. In the tested concentration range, the native ß‐HpH has no effect on the cytotoxicity and migratory capacity of the two tested cell lines. [Chol][AA] induce rearrangement in the ß‐HpH molecule. The complexes characterize with decreased thermal stability and altered cytotoxicity. Their cytotoxicity toward MDA‐MB‐231 cells is preserved or enhanced. At the highest assayed concentration, β‐HpH‐[Chol][Trp] produced the same cytotoxic effect against MDA‐MB‐231 cells as that reported for doxorubicin. Oppositely, the native ß‐HpH, significantly stabilizes MCF‐7 cells and their metastatic potential was enhanced. Abstract : Cholinium‐based ionic liquids with non‐polar amino acid anions affect seriously the secondary structure and thermal stability of a hemocyanin from Helix pomatia . However, in some cases these structural changes of the protein resulted to an increase of its selectivity and cytotoxycity toward breast cancer cells.